A Story to Tell. Issue 2 (3rd July 2019) - Voss, Tony
Abstract : Although Sol Plaatje died in 1932 with many of his hopes for South Africa unfulfilled, he has not been forgotten by his fellow South Africans. In a new edition of his biography of Plaatje, Brian Willan, one of the scholars whose work revived interest in Plaatje in the 1980s, has written the life of a great South African for the new South Africa. He has made use of newly discovered documentary sources and oral memory and given us a nuanced account of a complex life. Despite suffering many disappointments and indignities, Plaatje left his countrymen and –women a rich legacy. The centenary of Native Life in South Africa (1916), still perhaps his best-known work, was celebrated in a collection of essays which testify to that work's profound reach and continuing relevance. Plaatje continues to speak to South Africa in a way we can all understand.